PEMBERDAYAAN MASYARAKAT MELALUI PENGKEMASAN AGROWISATA SALAK DI DESA SIBETAN KECAMATAN BEBANDEM KABUPATEN KARANGASEM - Widyatmaja, I. G. N.; Sri, A. A. P.; Wiraatmaja, I. W. (Buletin Udayana Mengabdi; Vol 15 No 2 (2016): Jurnal Udayana Mengabdi, 2016)
KKN-PPM which carried out in Desa Sibetan, Bebandem, Karangasem aims to provide a wide space for local people to organizes and improves the system of management of salak agro tourism and to increases the participation of local communities in tourism development in Desa Sibetan through the well – packaging of salak agro tourism. In order to increase the income of local communities in Sibetan village, it is important to held this community empowerment through the utilization of its potencies, and then package it, as a valuable tourism product as well as to improve the finance and the power sources of those communities, also as a support of the tourism development in Karangasem. The targets of the activities of KKN – PPM are the agro tourism manager and the young generations of Sibetan village. The approaching models are: 1. Participatory Rural Appraisal (PRA) Model, (2) Entrepreneurship Capacity Building (ECB) Model, (3) Knowledge/Technology Transfer Model. Some activities have been done in KKN – PPM program in Desa Sibetan, in order to address the various problems of salak agro – tourism faced by the local communities of Sibetan village, such as: Setting – up a sort of a foundation to manage the agro – tourism in Desa Sibetan, tour guide traning for the local comunities, packaging training in how to package the salak processed products into tourism products, English for tourism courses, and provide the local communities houses as home stays for the tourists.
Keywords: community service, empowerment, agro-tourism, community, tourism